Respuesta :
[tex]\huge \bf༆ Answer ༄[/tex]
Let's solve ~
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x + y = 15 \: \: \: \: \: (1)[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x - y = 3 \: \: \: \: \: (2)[/tex]
From adding both equations, we get ~
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x + y + x - y = 15 + 3[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:2x = 18[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x = 18 \div 2[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x = 9[/tex]
Now, plug the value of x in equation 1 to find the value of y ;
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:x + y = 15[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:9 + y = 15[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:y = 15 - 9[/tex]
[tex]{ \qquad{ \sf{ \dashrightarrow}}} \: \: \sf \:y = 6[/tex]
The value of y and x in the equation is 6 and 9 respectively
How to solve simultaneous equation
Given:
x + y = 15
x - y = 3
- Add both equations to eliminate y
x + x = 15 + 3
2x = 18
x = 18/2
x = 9
- substitute x = 9 into
x - y = 3
9 - y = 3
- y = 3 - 9
-y = -6
y = 6
Learn more about simultaneous equation:
https://brainly.com/question/16863577